Teachers' Strategies to Solve Students' Problems in English Online Learning During Covid-19 Pandemic at SMP PGRI Kasihan Bantul Yogyakarta - Yulening Aminda Bili; Rifki Irawan; Nailul Pamungkas (Universitas PGRI Yogyakarta, 2022)
The Covid-19 pandemic has brought many complaints and impacts on human activities, especially in the world of education. Until now, the Covid-19 pandemic caused by the Coronavirus still hits and spreads widely in the community. In this case, schools implement an online learning system or online from their respective homes. Online learning activities carried out by class VIII students at SMP PGRI Kasihan are learning activities that have never been carried out by students whose lack of knowledge and abilities regarding online learning.The purpose of this study was to find out the teacher's strategy to overcome student learning problems during online learning. This study uses a qualitative method approach that is used to obtain information on student learning constraints as a result of the Covid-19 pandemic on teaching and learning activities at SMP PGRI Kasihan. The data collection technique used observation, interviews, and documentation.The results that there are several obstacles experienced by students in online learning activities, namely not having mobile phones, internet quota fees, and not having social media platforms for example Zoom, Google Meet, and Google Classroom applications. The strategy used by teachers at SMP PGRI Kasihan to overcome students' learning difficultie in participating in online-based learning in class VIII is to hold meetings with students twice a week, providing encouragement and motivation.